Analisis Idul Fitri dan Rekonsiliasi Sosial: Studi Tentang Tradisi Silaturahmi dalam Masyarakat Desa Pagar Gunung - Maya Marisa Oktavia (GHAITSA : Islamic Education Journal, 2025)
This research explores the tradition of friendship during Eid al-Fitr in Pagar Gunung Village, Padang Guci Hulu, Kaur Regency, as a means of social reconciliation in society. Eid al-Fitr is an important moment for Muslims to forgive each other and strengthen relationships, as mandated in Q.S Al-Hujurat verse 10. This tradition not only increases togetherness, but also plays a vital role in resolving conflicts and building harmony. However, modernization and changes in lifestyle threaten the continuity of this tradition, because some people choose to celebrate Eid only with their immediate family or do not even return to the village. With a qualitative approach, this research examines how the tradition of friendship influences social reconciliation amidst social change. Data collection was carried out through observation and documentation studies, while data analysis used data reduction techniques to obtain relevant themes and patterns. It is hoped that the research results will provide an understanding of the importance of the tradition of friendship in strengthening social relations and offer solutions to maintain the sustainability of this tradition amidst the challenges of modernization.